Entre a letra e o nome: alfabetização de alunos em situação de fracasso escolar à partir de intervenção de orientação psicanalítica - Marlene Maria Machado da Silva (2008)
This research aims to locate the origin of the deadlock reached by students with a gap between age and learning level in the literacy process, based on what they have to say regarding their difficulties. It seeks to investigate the existing relationship between such a process, which starts with the writing of ones given name, and the students subjectivity. For that matter, we use a psychoanalysis-inspired clinical pedagogical diagnosis, as suggested by Santiago (2005), which enables one to identify whether learning stalemates arise out of a conceptual pedagogical order or of a subjective order, by retrieving the studentss intelectual trajectory. As a subsidy for the application of the clinical pedagogical diagnosis in children with literacy difficulties, we have retrieved the contributions of educators and psychoanalysts both on writing and on given names, namely those from Emília Ferreiro (Education) and Lacan (Psychoanalysis), as well as contributions and opinions from literacy teachers on the use of ones given name and on the impact thereof for students during the literacy process. The choice of a given name, as per this investigation, is due to its multifaceted aspect, which causes it to be a milestone in Education, especially in the beginning of a childs formative years, due to the activities of the literacy process, and in Psychoanalysis. Our bet is that the students opinions, during the clinical pedagogical diagnosis, can point out what pedagogical interventions can assist them in the articulation of the double role of meaning and object of ones given name, providing them with another avenue for symbolization, for possible symptomatic manifestations that otherwise appear as school failure.